Regulation of hBD-2, hBD-3, hCAP18/LL37, and Proinflammatory Cytokine Secretion by Human Milk Oligosaccharides in an Organotypic Oral Mucosal Model - Gürsoy Ulvi K; Salli Krista; Söderling Eva; Gürsoy Mervi; Hirvonen Johanna; Ouwehand Arthur (Switzerland, 2022)
Human milk oligosaccharides (HMOs), the third largest solid fraction in human milk, can modulate inflammation through Toll-like receptor signaling, but little is known about their immunomodulatory potential in the oral cavity. In this study, we determined whether the HMOs 2'-fucosyllactose (2'-FL) and 3-fucosyllactose (3-FL) regulate human-beta defensin (hBD)-2 and -3, cathelicidin (hCAP18/LL-37), and cytokine responses in human gingival cells using a three-dimensional oral mucosal culture model. The model was incubated with 0.1% or 1% 2'-FL and 3-FL, alone and in combination, for 5 or 24 h, and hBD-2, hBD-3, and hCAP18/LL-37 were analyzed by immunohistochemistry. The expression profiles of interleukin (IL)-1, IL-1RA, IL-8, and monocyte chemoattractant protein (MCP)-1 were determined by LUMINEX immunoassay. The combination of 1% 2'-FL and 1% 3-FL, and 1% 3-FL alone, for 24 h upregulated hBD-2 protein expression significantly (p < 0.001 and p = 0.016, respectively). No changes in the other antimicrobial peptides or proinflammatory cytokines were observed. Thus, 3-FL, alone and in combination with 2'-FL, stimulates oral mucosal secretion of hBD-2, without effecting a proinflammatory response when studied in an oral mucosal culture model.